International Liquidity in a Multipolar World - Eichengreen, Barry (American Economic Review, 2012)
Today's global monetary and financial system, to a remarkable extent, continues to rely on the U.S. dollar for international liquidity. This reflects the currency's historic role, the liquidity of American financial markets, and the absence of alternatives. But with the emergence of emerging markets, the capacity of the United States to provide safe assets will be outstripped by the growth of international transactions. It is thus likely that other large economies, presumably Europe and China, will eventually join the United States as sources of international liquidity and that other currencies will come to share the dollar's reserve-currency status.